Technology Transfer of O-(2-[18F] Fluoroethyl)-L-Tyrosine (IASOglio®) Radiopharmaceutical - Anna Notaro; Salvatore Limpido; Lucie Plougastel; Alessandro Zega; Mauro Telleschi; Mauro Quaglierini; Alessia Danti; Antonio Fiore; Letizia Guiducci; Michela Poli (Pharmaceuticals)
Background/Objectives: Gliomas, including the most aggressive subtype—glioblastoma multiforme, are brain tumors with an unfavorable prognosis and high mortality. Early diagnosis is essential to improve treatment efficacy. Positron emission tomography PET with O-(2-[18F] fluoroethyl)-L-tyrosine ([18F]FET) has been supported by clinical studies for its role in diagnosis and monitoring the disease. However, the low availability of [18F]FET in Italy has limited its use in clinical praxis. This study describes the technological transfer of the radiopharmaceutical IASOglio® (the commercial [18F]FET developed by Curium Pharma in Italy), with the aim of improving national access to this advanced diagnostic technology. Methods: Three consecutive batches were produced using the automated Trasis AllinOne module, and quality control was performed, including chemical and microbiological tests, to successfully validate the production process. Additionally, the stability of the radiopharmaceutical for its entire shelf life has been demonstrated with stability testing at 14 h after end of synthesis (EOS). Results: The production of [18F]FET achieved a non-corrected yield between 49% and 52%, with a corrected decay rate ranging from 73% to 79%. The process met the required quality specifications, including bio-burden control and filter integrity. The technological transfer was successfully completed, and production authorization was obtained from the Italian Medicines Agency (AIFA) for the Officina Farmaceutica of Institute of Clinical Physiology of the National Research Council (CNR-IFC) located in Pisa. Conclusions: Local production of [18F]FET in Italy marks a milestone in glioma diagnosis, thereby contributing to timely treatment and improved clinical outcomes.